Screening for cryptococcal antigenemia using the lateral flow assay in antiretroviral therapy-naïve HIV-positive adults at an Ethiopian hospital clinic - Reepalu, Anton; Balcha, Taye T.; Yitbarek, Tadele; Jarso, Godana; Sturegård, Erik; Björkman, Per (BMC research notes, 2015)
Background Since treatment for latent cryptococcal infection (CI) before starting antiretroviral therapy (ART) reduces mortality in HIV-infected subjects, screening for cryptococcal antigen (CrAg) in blood is recommended for individuals with CD4 cell counts < 100 cells/µL in regions with high CI prevalence. We assessed CrAg screening using the lateral flow assay in HIV-infected adults eligible for ART in central Ethiopia. Results HIV-positive patients (age ≥ 18 years, CD4 cell count < 350 cells/μL and/or WHO stage IV, no current or previous ART) were recruited at Adama Regional Hospital, Ethiopia (February 2013 until March 2014). CrAg was determined in plasma by lateral flow assay. Among 129 included participants (median age 35 years, 64 % female) the median CD4 cell count was 210 cells/μL (interquartile range 110–309); 29 (23 %) had CD4 cell count < 100 cells/μL. Two (1.6 %) participants were CrAg-positive (CD4 cell counts 171 vs. 250 cells/µL), one of whom had clinically manifest cryptococcal meningitis at the time of testing. Conclusions In contrast to two recent reports from Ethiopia, we found few cases of CI among ART-naïve adults. Our study, which is the first using lateral flow assay for CrAg screening in this country, illustrates the need of larger surveys of CI prevalence among ART-naïve patients before defining recommendations on CI screening.